Thromboembolic Complications During Endovascular Treatment of Ruptured Intracranial Aneurysms – Prevention and Therapy - Baptista, Tiago (2012)
Thromboembolic phenomena are the most commonly reported complications during endovascular treatment of intracranial aneurysms with coils. Frequency of this complication varies in the literature, but authors reported rates ranging from 2.5 to 28%. Several mechanisms may be involved in the formation and migration of thrombus: it may be already existing inside the aneurysm and be dislocated and then migrate distally; it can be formed on the surface of the coils or catheters used, or it can appear in the remnant aneurysm sac it. Studies have shown a higher incidence of thromboembolic complications in wide neck aneurysms. In this paper we discuss the importance of prevention of thromboembolic complications during and after endovascular treatment of ruptured intracranial aneurysms. We also refer options and strategies to adopt in the event of a vascular occlusion is detected during the procedure, as the administration of inhibitors of glycoprotein IIb/IIIa or the release of an intra-cranial stent. Illustrative cases are shown. The prevention of thromboembolic complications and rapid action after the vascular occlusion is essential in order to improve the prognosis of patients undergoing endovascular treatment of ruptured intracranial aneurysms. Extensive knowledge of available options is essential to the pursuit of that goal.